Peran Pendidikan Agama Islam dalam Membentuk Karakter Religius dan Moral Siswa - Rozi, Bahru (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Islamic Religious Education (IRE) plays an important role in shaping students' character, especially amid increasing moral challenges in the modern era. This study aims to analyze effective strategies for strengthening PAI in supporting the development of students' religious and moral character in the school environment. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation review in secondary education institutions. The results of the study indicate that the success of PAI in shaping character is determined by four main interrelated aspects, namely strengthening values-based curricula and direct practice, applying active and contextual learning methods, improving the competence and exemplary behavior of PAI teachers, and establishing a consistent religious school culture. The conclusion of the study confirms that PAI will function optimally if it runs as an integrated system that not only teaches religious knowledge but also internalizes values into concrete actions. This study contributes to providing a strategic framework for schools to implement PAI-based character education more effectively.